Blockade of CTLA-4 on CD4+CD25+ regulatory T cells abrogates their function in vivo. - Read, S; Greenwald, R; Izcue, A; Robinson, N; Mandelbrot, D; Francisco, L; Sharpe, A; Powrie, F (2006)
Naturally occurring CD4+ regulatory T cells (T(R)) that express CD25 and the transcription factor FoxP3 play a key role in immune homeostasis, preventing immune pathological responses to self and foreign Ags. CTLA-4 is expressed by a high percentage of these cells, and is often considered as a marker for T(R) in experimental and clinical analysis. However, it has not yet been proven that CTLA-4 has a direct role in T(R) function. In this study, using a T cell-mediated colitis model, we demonstrate that anti-CTLA-4 mAb treatment inhibits T(R) function in vivo via direct effects on CTLA-4-expressing T(R), and not via hyperactivation of colitogenic effector T cells. Although anti-CTLA-4 mAb treatment completely inhibits T(R) function, it does not reduce T(R) numbers or their homing to the GALT, suggesting the Ab mediates its function by blockade of a signal required for T(R) activity. In contrast to the striking effect of the Ab, CTLA-4-deficient mice can produce functional T(R), suggesting that under some circumstances other immune regulatory mechanisms, including the production of IL-10, are able to compensate for the loss of the CTLA-4-mediated pathway. This study provides direct evidence that CTLA-4 has a specific, nonredundant role in the function of normal T(R). This role has to be taken into account when targeting CTLA-4 for therapeutic purposes, as such a strategy will not only boost effector T cell responses, but might also break T(R)-mediated self-tolerance.